La mediación, el arbitraje y el papel del defensor del pueblo en la solución de conflictos en el sistema jurídico ecuatoriano - Hinojosa Betancourt, Lina (2015)
This research is an issue of transcendental importance in our society that needs to be accepted and understood by those we are engaged in the field of law to establish aspects that will give a solution to the conflict in relation to the improvement of management will be addressed Justice Mediation arbitration and the Ombudsman is a solution of the conflict, it constitutes an alternative to resolve disputes between suppliers and consumers, but despite being constant legal concepts in our law, have failed to legitimize the environment of society, here is another of the challenges is doomed our country and how they solve their problems are the points where the investigation into the importance of publicizing what are the most common problems are in focus population, which are groups of people over the ways conflicts are solved and all those involved to resolve these. In our research, I will make an analysis of alternative methods of dispute resolution to the opinions of different authors and writers and illustrious writers who will give us a broader and deeper insight into our research topic and the role that the Ombudsman has in these cases. For this work of scientific-legal research have a content that achieves the fundamental objective is to find and central and legal regulations in the Organic Law of consumers and users, so that the Ombudsman be granted the power to your Proceedings of agreement are considered final judgment and res judicata and in case of default the Civil Judge requested execution. The problems are caused by the conflict of interest between people which is very natural in human relations because everyone seeks his own benefit. The way to solve the problems are different according to each culture to the rules governing the population, some may voluntarily seek a peaceful solution and hence the importance of the application of alternative methods of dispute resolution that our study will They are typecast between suppliers and consumers. And as usual the competition in the Organic Law on Consumer and User mainly in Art. 81, 82 and 83 which empowers the jurisdiction and procedure to the Ombudsman